2020
DOI: 10.1155/2020/7426461
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network Based Intelligent Support Model for Program Code Completion

Abstract: In recent years, millions of source codes are generated in different languages on a daily basis all over the world. A deep neural network-based intelligent support model for source code completion would be a great advantage in software engineering and programming education fields. Vast numbers of syntax, logical, and other critical errors that cannot be detected by normal compilers continue to exist in source codes, and the development of an intelligent evaluation methodology that does not rely on manual compi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…Experimental results, obtained by tuning the various hyper parameters and settings of the network, showed that both models achieved better results for bug detection and code completion in comparison with other related models. In [20,23], the authors proposed error detection, logic error detection, and the classification of source codes on the basis of an LSTM model. Both approaches used an attention mechanism that enhanced model scalability.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results, obtained by tuning the various hyper parameters and settings of the network, showed that both models achieved better results for bug detection and code completion in comparison with other related models. In [20,23], the authors proposed error detection, logic error detection, and the classification of source codes on the basis of an LSTM model. Both approaches used an attention mechanism that enhanced model scalability.…”
Section: Related Workmentioning
confidence: 99%
“…A variety of source code and software engineering methods have been proposed, such as source code classification [12,13], code clone detection [14,15], defect prediction [16], program repair [17,18], and code completion [19,20]. Recently, natural language processing (NLP) has been used in a number of domains, including speech recognition, language processing, and machine translation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the approaches employed existing benchmarks and datasets. Rahman et al [255] trained their proposed model using the data extracted from Aizu Online Judge (aoj) system. Liu et al [191], Liu et al [192] performed experiments on three real-world datasets to evaluate the effectiveness of their model when compared with the state-of-the-art approaches.…”
Section: Data Collectionmentioning
confidence: 99%
“…Many universities have created their own automated program assessment (APA) systems for programming courses to accelerate students' learning [12]- [14]. As a result, a large number of programmingrelated submission logs are created every day by OJ or APA systems in various organizations worldwide, which can be valuable resources for research and analysis [15], [16]. Therefore, this research aims to use programming-related resources (submission logs) for empirical research and analysis.…”
Section: Introductionmentioning
confidence: 99%